Effect of food supply on reproductive potential of Eretmocerus warrae (Hymenoptera Aphelinidae) - Hanan, A.; He, X.Z.; Shakeel, M.; Wang, Q. (New Zealand Plant Protection, 2010)
Eretmocerus warrae (Naumann Schmit) is a thelytokous parasitoid of greenhouse whitefly Trialeurodes vaporariorum (Westwood) It was first detected in New Zealand in 1997 during a survey of greenhouses in Auckland Under 221C 605 RH and 168 h lightdark the effect of food supply on longevity host feeding fecundity and parasitism in E warrae was investigated with four treatments (1) no food and no host (2) 10 honey solution and no host (3) 40 2nd instar nymphs per day and no honey and (4) 40 2nd instar nymphs per day and 10 honey solution Results showed that parasitoids lived significantly longer when given honey but no host (88 days) than parasitoids given the other treatments (2555 days) (P